Understanding Flu Vaccination in a Competitive Context: Influence of Alternative Flu Prevention Strategies on Flu Vaccine Uptake. (December 2017) - Ulasevich, Alec; Jacobs, Samantha; Mbangdadji, Djass; van Over, Max; Steffens, Lani
The flu causes a significant number of largely vaccine-preventable hospitalizations and deaths each year. Previous studies show that efficacy beliefs about other flu prevention strategies may be barriers to flu vaccine uptake. The purpose of this study was to assess attitudes and behaviors regarding flu vaccination and other flu prevention strategies and to examine the decision to get a flu vaccine within a competitive context. Two independent surveys were administered in 2013 (general population, n = 1, 158) and 2015 (millennial panel, n = 1, 574) among adults in the United States, which generated propensity models to get flu vaccines. Compared to the vaccine, participants considered many strategies to be more effective at preventing seasonal flu, particularly behaviors related to maintaining a strong immune system. Propensity models demonstrate that perceived effectiveness of some alternative "healthy behaviors" in a competitive set were associated with a lower likelihood of vaccine uptake. Results suggest that adults' engagement in alternative strategies may be at the expense of getting vaccinated. Social marketers should consider competition not just from unhealthy behaviors but from alternative healthy behaviors when designing programs and campaigns to ensure effectiveness of their messages.